Artificial Sweeteners Reveal Septic System Effluent in Rural Groundwater. Issue 6 (1st November 2017) - Spoelstra, John; Senger, Natalie D.; Schiff, Sherry L.
Abstract : It has been widely documented that municipal wastewater treatment plant effluents are a major source of artificial sweeteners to surface waters. However, in rural areas, the extent to which septic systems contribute these same compounds to groundwater aquifers is largely unknown. We examined the occurrence of four commonly used artificial sweeteners in an unconfined sand aquifer that serves as a water supply for rural residents, as a receptor of domestic wastewater from septic systems, and as a source of baseflow to the Nottawasaga River, ON, Canada. Groundwater from the Lake Algonquin Sand Aquifer in the southern Nottawasaga River Watershed was collected from private domestic wells and as groundwater seeps discharging along the banks of the Nottawasaga River. Approximately 30% of samples had detectable levels of one or more artificial sweeteners, indicating the presence of water derived from septic system effluent. Using acesulfame concentrations to estimate the fraction of septic effluent in groundwater samples, ∼3.4 to 13.6% of the domestic wells had 1% or more of their well water being derived from septic system effluent. Similarly, 2.0 to 4.7% of the groundwater seeps had a septic effluent contribution of 1% or more. No relationship was found between the concentration of acesulfame and the concentration of nitrate, ammonium, or soluble reactive phosphorus in the groundwater, indicating that septic effluent is not the dominant source of nutrients in the aquifer. It is expected that the occurrence of artificial sweeteners in shallow groundwater is widespread throughout rural areas in Canada. Core Ideas: Samples were collected from domestic wells and groundwater seeps in rural Ontario. Artificial sweeteners were found in >30% of rural groundwater samples. Acesulfame was used to estimate the fraction of septic effluent in groundwater. Septic effluent was not a significant source of nutrients in the aquifer.